The ‘Smart City’ between urban narrative and empty signifier: Hong Kong in focus - Alistair Cole; Dionysios Stivas; Emilie Tran; Calvin Lai (Cogent Social Sciences)
The article consists in an in-depth interpretative study of Smart City in the case of the Special Administrative Region of Hong Kong, China. It proposes a framework of analysis as a heuristic tool to interpret narratives in general and those of Smart City Hong Kong in particular. The capacity of a narrative to confer meaning draws upon three criteria: its originality (degree of endogeneity); its sincerity (internal validity and trustworthiness), and its extension (its ability to provide a convincing account to the outside world for social phenomena). They are also affected by the form of diffusion and communication. Four types of account emerged from our empirical investigation: survey responses; written responses from official agencies; face to face interviews; and collective interviews in focus groups. By reconstituting chains of meaning in relation to the Smart City, the article interrogates the utility of technology, sustainability and e-governance narratives for public administration. Taken as a whole, Smart City appears as a rather hollow narrative, an empty signifier, a general term lacking clear meaning.